Formation of a specific biological cycle in young skiers-racers and biathletes 11–15 years, depending on the level and direction of physical activity - Уткіна, Олександра (Slobozhanskyi Herald of Science and Sport, 2019)
Aleksandra Utkina The article presents the results of the analysis of the ratio of the training process according to the types of training and the performed cyclic physical activity and their influence on the formation of a specific biological cycle in female skiers-racers and biathletes 11–15 years old at the initial training stage and preliminary basic training. Purpose: to analyze the cyclic physical activity performed during the annual macrocycle in the period of the formation of a specific biological cycle of female skiers-racers and biathletes for 11, 12, 13, 14 and 15 years. Material & Methods: analysis of literary sources and planning documents, self-control diaries; survey and questioning; methods of mathematical statistics. In total, 88 young athletes of different ages took part in the study. The respondents included: skiers-racers 11–15 years old, biathletes 11–15 years old, trainers. Results: features of the formation of menstrual function in female skiers-racers and biathletes 11–15 years of age under the influence of a specific load were determined. Conclusions: out of 42 female skiers-racers aged 11–15 years, 53% had no menstruation, 29% had menarche or 1–2 menstruation, 12% had irregular menstruations and 5% had regular menstruations, and also from 46 female athletes 55% have no menstruation, 23% have menarche or 1–2 menstruation, 19% have irregular menstruation, and only 3% have regular menstruation.